P259 Psychological symptoms and job demands among shift workers. (1st September 2016) - Chu, Po-Ching
Abstract : Introduction: Because globalisation has a major influence on the electronic industry, understanding the mental health for shift workers at this industry is crucial for preventive strategy. The aim of the study is to assess the association between psychological symptoms and job demands for shift workers at an electronic enterprise in Taiwan. Methods: The study design is cross-sectional study with the self-reported questionnaire survey. Workers with history of any previous psychological disorder was not included, and there were 458 employees have completed the questionnaire. The items of the questionnaire include basic demographic data, past medical histories, family histories, personal habits, subjective symptoms (psychological symptoms and non-psychological symptoms), and job demands. The job demands is based on "hazard: stress at work" at the Risk assessment essentials of European Agency for Safety and Health at Work. The major outcome are depressive mood and anxiety mood. The association analysis were performed using simple and multiple logistic regression analysis. Results: 154 workers (33.6%) without history of any previous mental disorders had the psychological symptoms, which is depressive or anxiety. 166 (36.2%) of them are working with shift work. Psychological symptoms were statistical significant associated with job demands (work under high pressure, long working time, very high workload, unbalance between job demands and worker' abilities, conflicting demands, socially isolated) and regular exercise (more than twice per week). But age, gender, cigarette smoking, alcohol drinking did not show the association with psychological symptoms. Using multiple logistic regression analysis, job demands (work under high pressure (OR = 1.5), conflicting demands (OR = 2.2), socially isolated (OR = 2.9) and regular exercise (OR = 0.5) were associated with psychological symptoms. Discussion: For shift work workers at the electronic industry, intervention program for improving mental health should be focused on not only regular exercise but also special job demands.